European policies in the management of tuberculosis among migrants. (March 2017) - D'Ambrosio, Lia; Centis, Rosella; Dara, Masoud; Solovic, Ivan; Sulis, Giorgia; Zumla, Alimuddin; Migliori, Giovanni Battista
Highlights: The World Health Organization (WHO) reported that approximately 3% of the new tuberculosis (TB) incident cases and 25% of multidrug-resistant (MDR)-TB cases estimated to have occurred globally in 2015 were reported in the European Region. Over a quarter of TB cases in the European Union and European Economic Area (EU/EEA) are among foreign-born individuals. A better understanding of TB trends at the regional and sub-regional levels and of the existing policies on migrants and refugees is urgently needed. Policies and practices in force in the European countries with regard to the management of TB and latent TB infection among refugees upon arrival are described. Summary: Globally 10.4 million new tuberculosis (TB) incident cases were estimated to have occurred in 2015, of which 3% were reported in the World Health Organization European Region. Importantly, about 25% of the global multidrug-resistant TB (MDR-TB) cases are reported in the European Region, representing one of the greatest challenges to TB control; these are reported particularly in the countries of the Former Soviet Union. Over a quarter of TB cases in the European Union and European Economic Area (EU/EEA) are reported among foreign-born individuals. In line with the recent increase of migration flows towards Europe, TB among migrant populations is also on the rise, emphasizing the need for a better understanding of the TB trends at the regional and sub-regional levels, and of the existing policies on migrants and refugees. The present article is aimed at describing the policies and practices of European countries with a low and intermediate TB incidence with regard to the detection and management of TB and latent TB infection (LTBI) among refugees in Europe.